Ultra-conserved elements provide insights to the biogeographic patterns of three benthic macroinvertebrate species in the Baltic Sea. (5th July 2022) - Petersen, H. Cecilie; Knott, K. Emily; Banta, Gary T.; Hansen, Benni W.
Abstract: The Baltic Sea, with its steep salinity gradient, high water retention time, and relatively young age, represents a marginal ecosystem between marine and freshwater extremes. Due to differing invasion history and dispersal capabilities of Baltic species, there are large differences in species distributions, species-specific genetic structure and variation, and edge populations that may represent both a subset of the original population, as well as unique genetic lineages. We used a phylogenomic approach to investigate relationships between populations of three benthic macroinvertebrate species: Pygospio elegans, Corophium volutator, and Mya arenaria, providing new insight into evolutionary dynamics among populations in the Baltic Sea and the adjacent North Sea. We found little relation among the populations of P. elegans and C. volutator, in contrast to M. arenaria, which exhibits a higher degree of resemblance between populations. We also found low relation within sites sampled at different times of the year for all species. Each species exhibited unique phylogenetic patterns, suggesting the North Sea populations of P. elegans and M. arenaria are closely related to populations within the Baltic Sea, and with only C. volutator showing trends resembling isolation by distance. These differences could be explained by both their different invasion histories and dispersal capabilities of the individual species. Highlights: First population study of marine macroinvertebrates using ultra-conserved elements. New insight into population dynamics of three macrofauna species in the Baltic Sea. Divergence within populations varies between macrofauna species in the Baltic Sea . High temporal divergence was observed for all species. Divergence variances related to species-specific invasion and dispersal potential.